Staphylococcus aureus Extracellular Vesicles Elicit an Immunostimulatory Response in vivo on the Murine Mammary Gland - Tartaglia, Natayme R.; Breyne, Koen; Meyer, Evelyne; Cauty, Chantal; Jardin, Julien; Chrétien, Denis; Dupont, Aurélien; Demeyere, Kristel; Berkova, Nadia; Azevedo, Vasco; Guédon, Eric; Le Loir, Yves (Frontiers in Cellular and Infection Microbiology, 2018)
Staphylococcus aureus is a major pathogen responsible for bovine mastitis, the most common and costly disease affecting dairy cattle. S. aureus naturally releases extracellular vesicles (EVs) during its growth. EVs play an important role in the bacteria-bacteria and bacteria-host interactions and are notably considered as nanocarriers that deliver virulence factors to the host tissues. Whether EVs play a role in a mastitis context is still unknown. In this work, we showed that S. aureus Newbould 305 (N305), a bovine mastitis isolate, has the ability to generate EVs in vitro with a designated protein content. Purified S. aureus N305-secreted EVs were not cytotoxic when tested in vitro on MAC-T and PS, two bovine mammary epithelial cell lines. However, they induced the gene expression of inflammatory cytokines at levels similar to those induced by live S. aureus N305. The in vivo immune response to purified S. aureus N305-secreted EVs was tested in a mouse model for bovine mastitis and their immunogenic effect was compared to that of live S. aureus N305, heat-killed S. aureus N305 and to S. aureus lipoteichoic acid (LTA). Clinical and histopathological signs were evaluated and pro-inflammatory and chemotactic cytokine levels were measured in the mammary gland 24 hour post-inoculation. Live S. aureus induced a significantly stronger inflammatory response than that of any other condition tested. Nevertheless, S. aureus N305-secreted EVs induced a dose-dependent neutrophil recruitment and the production of a selected set of pro-inflammatory mediators as well as chemokines. This immune response elicited by intramammary S. aureus N305-secreted EVs was comparable to that of heat-killed S. aureus N305 and, partly, by LTA. These results demonstrated that S. aureus N305-secreted EVs induce a mild inflammatory response distinct from the live pathogen after intramammary injection. Overall, our combined in vitro and in vivo data suggest that EVs are worth to be investigated to better understand the S. aureus pathogenesis and are relevant tools to develop strategies against bovine S. aureus mastitis.